Think-Talk-Write: Integrating Reading With Writing Explanation Text - Novitasari, Putri; Misela, Jenny Ika (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
The objective of this study was to find out whether there was significanct impact of think-talk-write (TTW) to improve students writing on explanataion text. By this research, researcher aplied think-talk-write method to boost students’ skill in writing explanation text. This research conducted by implementing TTW method in which the students passed some steps such as, they were instructed to read an article, think about the information, talk in pairs, and write the paragraph.  Quantitative research was implemented as the research design. The sample was students of eleventh grade which contained of  49 students for experimental class and 47 students of control class. The data from the pre-test showed that both classes had a slight difference in the mean score, where experimental class got 67,43 and the control class got 57,83. However, the post-test score showed that the experimental class got a higher mean score 92,88 than the control class 75,47. In addition, the result of the post-test score revealed that the score of experimental class was higher than the controlled class. The increasing of mean score proved that there was improvement on students’ writing in composing explanation text by applying think-talk-write method for teaching and learning proccess.